The finding of native tungsten microcrystals in Bilokorovychi proterozoic conglomerates of the Volyn - Kvasnytsya, V.M.; Pavliuk, O.V.; Kvasnytsya, I.V.; Vysotskyi, B. L.; Gurnenko, I.V. (Reports of the National Academy of Sciences of Ukraine, 2014)
Microcrystals of native tungsten on grains of native gold from Bilokorovychi proterozoic conglomerates of the Volyn region have been established. They are somewhat flattened perfect octahedrons (?); their sizes are from 2 to 10 microns. The tungsten crystals are the first discovery of polyhedrons of this mineral in Ukraine and, perhaps, are the second discovery in the world. They are closely associated with nano-microcrystals of secondary native gold, which grows on the original grains of native gold. The tungsten microcrystals contain almost no impurities, sometimes only to 0.16 wt. % of chromium. Probably, as a secondary gold, the tungsten microcrystals were formed in situ during the formation of Bilokorovychi conglomerates. The comparison of the extremely rare mineral by the basic features found in the various geological environments has been made.